Kompleksnost, literatura, znanost - Škulj, Jola (Primerjalna književnost, 2012)
Deep insights into the complex poetic system of modernism, a period founded during key historical shifts when views on language (as a system of signs) and its crucial role were newly valorised and the idea of point of view became thought-provoking for literature and arts as well as hard sciences (say, for Heisenberg), help shed new light on the role of humanities, later discussed in the rethinking of sciences by Nowotny et al. as one of five concrete contexts for the new production of knowledge in effective science policies. Literature exists as a vital segment of our living phenomenology, and the process of reading texts is a direct encounter with our human autopoietic adaptation and our own identity questioning. Two points are considered: autopoiesis and its sense in poiesis, and the potential of discourses in complex life dynamics.
Keywords: književnost; literature; science; znanost; humanistika; jezik in zavest; modernizem; samoreferenčnost; samorefleksivnost; dialog